2020
DOI: 10.22161/ijels.55.40
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Headmaster personality competence in developing competitive advantages: A Case Study in East Java, Indonesia

Abstract: The aim of this research is analyzing and describing about personality competence of principal in building school competitive advantage. This research approach uses qualitative approach to the type of case study research. Data collection techniques using in-depth interviews, participant observation, and documentation. The steps of data analysis consist of data collection, data reduction, data presentation, and drawing conclusions. Data validity checking techniques are carried out through credibility, dependabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…in Pringsewu Regency" is accepted. The results of this study are in accordance with the research of Azhad et al (2018) and Halima & Mardiana (2020) which concluded that organizational culture has an influence in increasing competitive advantage.…”
Section: Hypothesis R-value R-square T-count F-count Results Conclusionsupporting
confidence: 91%
“…in Pringsewu Regency" is accepted. The results of this study are in accordance with the research of Azhad et al (2018) and Halima & Mardiana (2020) which concluded that organizational culture has an influence in increasing competitive advantage.…”
Section: Hypothesis R-value R-square T-count F-count Results Conclusionsupporting
confidence: 91%